Survival and growth of 20 species of trees and shrubs on Appalachian surface mines. (9th May 2018) - Monteleone, Alexis; Skousen, Jeff; Shuler, Jamie; McDonald, Louis; Williams, Rick; Holaskova, Ida
Abstract: The Forestry Reclamation Approach recommends that 2 tree types be planted during reclamation reforestation projects to reclaim the site to a forest ecosystem. Late succession trees such as oaks ( Quercus ), maples ( Acer ), poplars ( Liriodendron ), and pines ( Pinus ) are planted as crop trees, but understory trees and shrubs of native forests are not often planted or planted in fewer numbers, so less is known of their survival and growth in mine soils. This study evaluated survival and growth of 20 species of small trees and shrubs planted on 4 surface mines in Appalachia. Survival and height were determined at the end of the first year after planting, and then again after 7 or 9 years depending on the site's planting date. Soil properties varied across sites with pH ranging from 3.8 to 7.5 and percent soil material (≤2 mm) ranging from 58% to 82%. Extracted nutrient concentrations (P, K, Ca, Mg, and S) were also variable across sites. Five of the 20 species had survival ≥50% (black chokeberry [ Aronia melanocarpa Michx.], black cherry [ Prunus serotina Ehrh.], Washington hawthorn [ Crataegus phaenopyrum L. f.], nannyberry [ Viburnum lentago L.], and hazelnut [ Corylus avellana L.]). Eleven species survived from 37% to 47% and 4 species experienced ≤30% survival. Almost all species at least doubled their height and many increased 3 to 4 times above their initial planted seedling height. The species that survived ≥50% are recommended for forestry plantings and those that survived ≥37% may be considered as candidates for planting during forestry reclamation.